2018
DOI: 10.14238/sp19.3.2017.150-5
|View full text |Cite
|
Sign up to set email alerts
|

Kadar 25-hydroxyvitamin D sebagai penanda sepsis pada anak

Abstract: Latar belakang. Sepsis merupakan penyebab tersering morbiditas dan mortalitas pada anak. Vitamin D memiliki peran penting dalam mengoptimalkan sistem imun bawaan serta memodulasi respon imun adaptif pada sepsis. Tujuan. Untuk mengevaluasi nilai diagnostik dari kadar 25-hydroxyvitamin D sebagai penanda sepsis pada anak. Metode. Penelitian diagnostik dengan desain potong lintang dilakukan terhadap 50 anak di PICU RSUP Haji Adam Malik dari Februari sampai Maret 2016. Duapuluh lima anak didiagnosis sepsis dan 25 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Vitamin D deficiency in neonates was correlated with neonatal sepsis incidence [15]. In several pediatrics studies, significant relationships were reported between Vitamin D deficiency and sepsis [16]. Kanth et al, (2016) reported the majority of neonates (64.1%) with neonatal sepsis were suffering from Vitamin D deficiency, and Vitamin D was statistically significant to neonatal sepsis (p = 0.05) [6].…”
Section: Discussionmentioning
confidence: 98%
“…Vitamin D deficiency in neonates was correlated with neonatal sepsis incidence [15]. In several pediatrics studies, significant relationships were reported between Vitamin D deficiency and sepsis [16]. Kanth et al, (2016) reported the majority of neonates (64.1%) with neonatal sepsis were suffering from Vitamin D deficiency, and Vitamin D was statistically significant to neonatal sepsis (p = 0.05) [6].…”
Section: Discussionmentioning
confidence: 98%